(untitled) (Journal of Architectural Design, 2022)
This article provides information on the funds spent on the restoration and repairrestoration works carried out in the objects of material cultural heritage in the Fergana region during 2018-2021. Before carrying out the repair and restoration of archaeological, architectural, monumental and interesting places, which are among the objects of material cultural heritage, the technical condition of the object was assessed